Biomarkers of oral inflammation in perinatally HIV‐infected and perinatally HIV‐exposed, uninfected youth. (5th September 2019) - Moscicki, Anna‐Barbara; Yao, Tzy‐Jyun; Russell, Jonathan S.; Farhat, Sepideh; Scott, Mark; Magpantay, Larry; Halec, Gordana; Shiboski, Caroline H.; Ryder, Mark I.; ,
Abstract: Aim: To examine oral biomarkers that have been associated with periodontal disease progression in HIV‐infected adults in perinatally HIV‐infected and HIV‐exposed but uninfected youth. Material and Methods: This was a cross‐sectional, multicentre substudy of youth participating in the Oral Health Pediatric HIV/AIDS Cohort study. Gingival crevicular fluid repository samples from participants with and without periodontal disease (using Gingival Index [GI] and Bleeding on Probing [BOP] parameters on dental examination) were tested for concentration levels of inflammatory biomarkers. Associations were assessed using Wilcoxon test and Spearman correlation. Results: For perinatal HIV youth ( n = 129), the markers consistently elevated ( p < .05) in sites with GI ≥2 and in sites with BOP were interleukin‐1β, 6 and 13, macrophage inflammatory protein‐1α and metalloproteinase‐9. Serum tumour necrosis factor‐α and soluble CD14 were positively correlated with a summary count of elevated cytokines. No associations were seen among HIV‐uninfected subjects ( n = 71). Conclusions: The association of oral biomarkers of inflammation with clinical indicators of periodontal inflammation and systemic immune activation suggests that perinatal HIV‐infected youth may be at higher risk for developing significant periodontal disease, associated with tooth loss and HIV progression. More frequent dental care of this group is needed to prevent potential periodontal progression.